Outcomes of surgical treatment with patterns of bacterial culture and antimicrobial susceptibility testing in cases of cervical abscessation in dogs: 82 cases (2018–2021) - Alexandra Walker; Nicole Amato; Jennifer Brisson; Samuel Stewart (BMC Research Notes, 2023)
Abstract Objective: The objective of this study was to summarize the presentation, diagnosis, and outcome for dogs surgically treated for chronic cervical abscessation following suspected or reported cervical or oropharyngeal trauma, as well as to report on culture results and antimicrobial susceptibility patterns. Results: Eighty-two dogs were identified by retrospective review. Successful surgical outcome was achieved in 92.7% of dogs. Abscess recurrence was confirmed or suspected in 6/82 (7.3%) cases, and surgical intervention for abscess recurrence was performed in 4/82 (4.9%) cases. Foreign material was identified at surgery in 5/82 (6%) cases. Incisional healing complications were noted in 9/82 (10.9%) cases and required additional surgery in 5/82 (6%) cases. Twenty-three (28%) dogs had negative culture results. The results of antimicrobial sensitivity testing led to a change in antimicrobial treatment in only 9% of cases. Surgically treated cervical abscessation carries a good prognosis with a low incidence of recurrence in this cohort (in contrast to previous reports), despite low frequency of foreign body removal or identification of the underlying cause of the abscess. Excision of chronic inflammatory tissue may not be necessary for a successful outcome, contrary to previous recommendations. Multi-pathogen infections and anaerobic infections are commonly encountered.